Taming the Zoonosis in Tropic: Rise of Rabies (hondsdolheid) as an Endemic Disease and Its Containment in Colonial Indonesia, 1870s-1930s - Wahid, Abdul (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: Rabies, or canine madness, is one of the most frequent zoonotic diseases, mainly through the bite of a dog. The disease presumably had been in existence long before the coming of Europeans, as raising a dog and other rabid animals had been a strong tradition among indigenous people. Yet, it was only in the mid19th Century, with the establishment of colonial administration, that rabies began to be recorded, and then only at the end of the Century did the colonial government perceive it as a dangerous disease, especially in Java. This study seeks to investigate why rabies became a public health issue only later at the end of the 19th Century. What factors influenced the rise of this disease, how did local people perceive it, and what was the colonial government's response to this disease? This paper argues that rabies was an endemic disease before the colonial authorities acknowledged it and that it continued until the end of the colonial period, based on colonial publications and other pertinent sources, mainly newspapers. The limited records and belated development and introduction of medical science became contributing factors to the tardiness of government responses in resolving this endemic disease. Rabies remained a threatening public issue after Indonesia became independent. Abstrak: Rabies, atau penyakit anjing gila, merupakan salah satu penyakit zoonosis yang paling sering terjadi, terutama melalui gigitan anjing. Penyakit ini mungkin sudah ada jauh sebelum kedatangan bangsa Eropa, karena memelihara anjing dan hewan lain yang terkena rabies merupakan tradisi yang kuat di kalangan penduduk asli. Namun, baru pada pertengahan abad ke-19, dengan berdirinya pemerintahan kolonial, rabies mulai tercatat, dan baru pada akhir abad tersebut pemerintah kolonial menganggapnya sebagai penyakit berbahaya, terutama di Jawa. Penelitian ini berupaya menyelidiki mengapa rabies baru menjadi masalah kesehatan masyarakat pada akhir abad ke-19. Faktor-faktor apa yang memengaruhi munculnya penyakit ini, bagaimana masyarakat setempat melihatnya, dan apa tanggapan pemerintah kolonial terhadap penyakit ini? Tulisan ini berpendapat bahwa rabies merupakan penyakit endemik sebelum pemerintah kolonial mengakuinya dan penyakit ini terus berlanjut hingga akhir masa kolonial, berdasarkan publikasi kolonial dan sumber-sumber terkait lainnya, terutama surat kabar. Keterbatasan data dan keterlambatan pengembangan serta pengenalan ilmu kedokteran menjadi faktor yang menyebabkan lambatnya respons pemerintah dalam mengatasi penyakit endemik ini. Rabies tetap menjadi masalah publik yang mengancam setelah Indonesia merdeka.